Biochemical and structural comparative study between bird and mammal pancreatic colipases - Abir Ben Bacha (Journal of Lipid Research, 2006)
Three colipases were purified from pancreas of two birds (ostrich and turkey) and one mammal (dromedary). After acidic and/or heat treatment and precipitation by sulfate ammonium and then ethanol, cofactors were purified by Sephadex G-50 gel filtration followed by ion-exchange chromatography first on Mono S and then on Mono Q. One molecular form was obtained from each species with a molecular mass of ∼10 kDa. Cofactors were not glycosylated. The N-terminal sequences of the three purified cofactors showed high sequence homology. A 90 amino acid sequence of the ostrich cofactor was established based on peptide sequences from four different digests of the denaturated protein using trypsin, chymotrypsin, thermolysin, or staphylococcal protease. This sequence exhibited a high degree of homology with chicken and mammal cofactors. Bile salt-inhibited pancreatic lipases from five species were activated to variable extents by colipases from bird and mammal origins. The bird pancreatic lipase-colipase system appears to be functionally similar to homologous lipolytic systems from higher mammals. Our comparative study showed that mammal colipase presents a lower activation level toward bird lipases than the bird counterpart. Three-dimensional modeling of ostrich colipase suggested a structural explanation of this fact.